Gender Equality in Imamate Shia and Sunni Inheritance Jurisprudence: A Comparative Analysis of Legal Doctrines and Familial Relationships - Elfia, Elfia; Surwati, Surwati; Nelli, Fitra; Fajri, Yan (Fakultas Syariah UINSI Samarinda, 2024)
The issue of inheritance has always been a focal point in society, particularly when addressing the bilateral principle, which ensures property distribution to male and female heirs in Islamic law. The difference in inheritance rights between men and women remains a subject of debate in both Sunni and Shia applications. Shia inheritance law emphasizes equity by granting women recognized inheritance rights alongside men at all levels, while Sunni law follows specific Quranic guidelines that often result in unequal shares. Shia jurisprudence accords women the same status and rights as men in terms of their recognition as legitimate heirs within the family hierarchy. This research examines the mechanisms of inheritance distribution in Shia jurisprudence through a gendered lens, focusing on its implications for women's rights and their position in Islamic inheritance frameworks. This normative legal research adopts a gendered approach to Islamic inheritance law. The secondary data related to Sunni and Shia inheritance rules were traced manually and online from OJS websites. The data were analyzed using content analysis and then narrated through data reduction, display, and verification techniques. The research found that the Shia concept of inheritance distribution involves two categories of heirs: dzawil furudh (heirs with fixed shares) and qarabah (relative heirs). Heirs not included as dzawil furudh (heirs with fixed shares) as specified in the Qur'an and Hadith are classified as qarabah, which includes both male and female relatives based on proximity to the deceased. In determining their rights, Shia addresses the issue of gender while still applying the provisions of the texts regarding the share of men and women. Men and women at the levels of descendants (furu'), parents (ushul), siblings, and parents' siblings (hawasyi) have recognized inheritance rights, with shares determined based on Quranic guidelines. Second, Shia inheritance law consistently applies the bilateral principle, ensuring that women are granted inheritance rights alongside men in accordance with the Quranic 2:1 distribution ratio. This highlights that from a gender perspective, Shia jurisprudence demonstrates a more inclusive approach toward women's inheritance rights, emphasizing equity and recognition within its legal framework.